Interpretation - Suddaby, Ian (Scottish Archaeological Internet Reports, 2009)
The evaluation has provide evidence for activity which, on artefactual grounds alone, spans six millennia, from the Neolithic to the 20th century. This long-term chronology can be refined to indicate two distinct phases of human burial on the knoll, firstly the short-cists and secondly the early medieval cemetery. Within the latter phase, three sub-phases were recognised, sandstone cists without lintels, volcanic stone cists with lintels and dug burials. There was no evidence of a hiatus within the sub-phases.